Asosiasi Varian Genetik Angiotensin Converting Enzyme ( ACE ) Terhadap Karakteristik Faktor Risiko Pada Penderita Stroke Iskemik di Rumah Sakit Umum Pusat Dr. Kariadi Semarang - Dodik Tugasworo Pramukarso; Herlina Suryawati; Soetedjo Soetedjo; Jimmy Eko Budi Hartono; Trianggoro Budisulistyo; Arinta Puspita Wati; Aditya Kurnianto; Patria Adri Wibhawa (RSUP Dr. Kariadi, 2021)
BACKGROUND : Stroke is the leading cause of death and disability in the world. The occurrence of ischemic stroke is indicated by genetic factors, environmental factors and the interaction between it. Angiotensin Converting Enzyme (ACE) genetic variant is associated with various characteristics of risk factors for ischemic stroke. OBJECTIVE : Identifying genetic variants of Angiotensin Converting Enzyme (ACE) with the Polymerase Chain Reaction (PCR) method and to find it’s correlation beetwen risk factor in patients with Ischemic Stroke at Dr. Kariadi Semarang METHOD : The subjects of the study were 72 patients with ishcemic stroke who were treated at the polyclinic of the Neurology Department Dr. Kariadi Semarang in January - December 2013. DNA extraction of research subjects was carried out at the Laboratory of the Center of Biomedical Research (CEBIOR), Faculty of Medicine, Diponegoro University from January to March 2020. Amplification using the Polymerase Chain Reaction (PCR) method was carried out using an Eppendorf thermocycler. Data were analyzed with SPSS for Windows Version 25 RESULT : 72 samples analyzed obtained genetic variants of ACE II 39 (54.2%) samples, genetic variants of ACE DI 30 samples (41.7%), and genetic variants of ACE DD 3 (4.2%) samples. Meanwhile, there was no significant relationship ( p>0,05 ) between genetic variants of ACE and the characteristics of risk factors for ischemic stroke, namely age, gender, Body Mass Index, smoking history, triglyceride levels, HDL levels, LDL levels, obesity and hypertension. CONCLUSION : There are three types of ACE genetic variants, including the ACE II genetic variant, the ACE DI genetic variant, and the ACE DD genetic variant. Among the three genetic variants, ACE II genetic variant is the most common variant and there is no significant relationship to the various risk factor characteristics found in ischemic stroke patients at Dr. Kariadi Gneeral Hospital Semarang.